Meningkatkan Semangat Belajar dan Kemampuan Calistung Anak Usia Dini di Panti Asuhan Mercy Clement Indonesia - Gaby Rolisa Teresia Tarigan; Malida Putri (Yayasan Literasi Sains Indonesia, 2022)
The Covid-19 pandemic condition affects the motivation and enthusiasm for learning in children, which is becoming increasingly low. Especially in the condition of the children in the orphanage, they have to learn independently to catch up with them which makes them bored with the learning atmosphere. This problem occurs in children at the Mercy Clement Indonesia Orphanage. The limited teaching and learning activities in schools make children have to learn independently. Of course, when learning independently, children will feel bored easily, and this happened to one of the children at the orphanage, so he needed help in order to revive his enthusiasm for learning. As a social welfare student who is in Field Practice (PKL) it is your responsibility to provide assistance. The method of assistance is carried out by social case work through several stages, namely Engagement, Intake, Contract (EIC), Assessment, Planning, Intervention, Evaluation and Termination. The solution for the help provided was a children's activity book, the Calistung Challenge Book. This book contains calistung exercises (reading, writing and counting), activity sheets such as stories, crosswords, interesting facts. The evaluation of this program was seen that the client felt enthusiastic in learning and understanding the lessons of calistung (reading, writing and counting).